Influence of Extraction Techniques on Betalain Yield and Bioactive Phytochemical Analysis of Nopal Fruit Peels - Karunanithi, Anbarasi (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Nopal fruits (Opuntia ficus-indica) and their peels contain significant amount of natural colorants which can be used in food and pharmaceutical applications instead of using synthetic dyes. Materials and Methods: The present study focuses on the extraction of betalain from nopal fruit peel by conventional and Ultrasound-Assisted Extraction (UAE) and optimizing the UAE process variables using Box Box-Behnken surface design, as well as a preliminary screening of valuable phytochemicals using Gas-Chromatography and Mass Spectroscopy (GC-MS) which contribute to the medicinal potential of nopal fruits. Results: Soxhlet extraction of Betacyanin and Betaxanthin (BC and BX) was found to be 4.51 mg/g of BC and 0.67 mg/g of BX. The extraction yield of betacyanin and betaxanthin for UAE was extracted at 16 min, 40°C, 1/22 g/mL, and the yield was found to be 3.00 ± 0.23 mg/g BC, 0.225 ± 0.02 mg/g BX. Conclusion: GC-MS analysis of nopal fruit (Opuntia ficus-indica) peel revealed that ethanol extracts of nopal fruit peel revealed two fold higher results of - (+)-Ascorbic acid 2, 6-dihexadecanoate of UAE than soxhlet. Also other phytochemicals such as n-Hexadecanoic acid (Palmitic acid) which posses anti-inflammatory, antibacterial and antifungal activity are found to be higher.
Keywords: Natural colorant; Ultrasound-assisted extraction; Response surface methodology; Anti-inflammatory; Anti-bacterial